Implementasi Metode Spiral dalam Pengembangan Sistem Informasi Desa untuk Meningkatkan Keterbukaan Informasi Publik di Desa Brengkok - Lutfiyani, Anisa; fersellia, fersellia; Idris, Achmad Choerul Umam Nur; Salikhan, Salikhan; Rokhayati, Rani; Mustikaningsih, Ajar (Jurnal Kridatama Sains dan Teknologi, 2024)
Advances in information technology have had a significant impact on village government management, especially in supporting open public information and efficient services. This research explores the implementation of the Spiral Method in developing the Village Information System (SID) to increase transparency in Brengkok Village. The spiral method was chosen because of its flexible iterative approach, allowing the development of a system that is adaptive to user needs. Data collection was carried out through interviews, observations and questionnaires to identify village information needs. The system developed includes main features such as Homepage, Village Profile, Village Government, Village Data, Regulations, Maps, Developing Village Index (IDM), and Admin module. The implementation results show that the spiral method is effective in producing a system that suits village needs, with features that support information accessibility, citizen interaction, and secure data management. This web-based information system is able to increase transparency, public participation, and make it easier for residents to access village information. This research recommends further development with interactive features and technical infrastructure improvements to support system sustainability. Thus, the Village Information System based on the Spiral Method makes a real contribution to realizing a more open, efficient and accountable village government.